Effect of Development Passion on Environmental Sustainability: Augmenting the Process through Effectuation (Journal of Asian Development Studies, 2024)
This paper studies the effect of the development of passion on environmental sustainability and the effect of effectuation as a mediator. Effectuation is gaining popularity among the research community due to its practicality and effectiveness. The samples of 348 respondents were collected to measure the three variables and their relationship. The study uses a self-reported instrument to gauge the effect of Entrepreneurial passion on enterprise environmental sustainability and the impact of effectuation as a mediator. SPSS version 25 is used for statistical analysis, and the Hayes process is employed for obtaining the mediation results. The study finds a strong link between effectuation as a mediator on enterprise environmental sustainability and recommends using the model of effectuation as a process for sustainability outcomes. Enterprise sustainability, economic or environmental is not linear and hence needs passion and resilience. The Effectuation process assists the passionate entrepreneur in employing his/her available resources to enhance their outcomes to achieve enterprise environment sustainability. This research adds to the current literature on how effectuation can become a process of environmental sustainability. It is observed that little studies are found on development passion and this study will augment the literature on development passion and its impact on environmental sustainability. This research recommends the suggestions of the effectuation model which proposes that an entrepreneur needs to develop a network for environmental sustainability instead of trying to do everything by them self.